Experimental and numerical investigation on size effect on crushing behaviors of single calcareous sand particles. Issue 5 (4th May 2021) - Kuang, Dumin; Long, Zhilin; Guo, Ruiqi; Yu, Piaoyi
Abstract: Single particle crushing tests were conducted to investigate the size effect on the crushing behaviors of single calcareous sand particles experimentally and numerically. The particle crushing strengths and fragmentation modes of the calcareous sand particles with six different size groups (5–17 mm) were investigated. Moreover, the numerical simulation based on discrete element method was performed to assess the progressive fracture behavior. The particle crushing strength data are found to be satisfy the Weibull's statistics model well. The Weibull modulus decreases with the increasing particle size. Meanwhile, the scaling law between the characteristic crushing strength and the particle size is smaller than the theoretical predication by the Weibull model. As the particle size increases, the fragmentation mode changes from simultaneous splitting and successive splitting to primary splitting. Furthermore, the numerical results reveal that the fractures occur firstly in the contact area between the loading walls and the top and bottom ends of the particles, eventually forming the penetrative fracture zones along the direction of loading.